Fibrin gel versus papain gel in the healing of chronic venous ulcers: A double-blind randomized controlled trial - de Araújo, Illymack CF [UNESP]; Defune, Elenice [UNESP]; Abbade, Luciana PF [UNESP]; Miot, Hélio A [UNESP]; Bertanha, Matheus [UNESP]; de Carvalho, Lídia R [UNESP]; Ferreira, Rosana R [UNESP]; Yoshida, Winston B [UNESP] (SAGE Publications, 2017)
Objectives: Compare the efficacy and safety of fibrin gel to 8% papain gel for wound dressing of venous ulcers. Method: Patients with chronic venous ulcers were randomly assigned to one in three groups: Group 1—fibrin gel; Group 2—8% papain gel; Group 3—carbopol gel (control). Patients were seen every 15 days during 2 months, verifying reduction of the ulcer area, local infection, exudation, and epithelization. All serious or nonserious adverse events were recorded. Results: Fifty-five patients (total of 63 ulcers) were randomly distributed in three groups (G1 = 21; G2 = 19; G3 = 23). No patient was excluded or discontinued treatment throughout the study. The areas of the ulcers were similarly reduced in all groups (14.3%, 21.1%, and 30.4% in groups 1, 2, and 3, respectively), and all had significant reduction in exudation and contamination. Conclusion: The data demonstrate that neither fibrin gel nor papain gel were able to improve the process of ulcer-healing, as compared to control.
Keywords: fibrin modulating agents; papain; Varicose ulcer; venous insufficiency; wound healing